2016
DOI: 10.4149/gpb_2016015
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between the effect of 17-β estradiol and angiotensin converting enzyme inhibitor on osteoporosis in ovariectomized rats

Abstract: Osteoprotegerin (OPG) and receptor activator of nuclear factor-kappa B ligand (RANKL) have been revealed in the pathogenesis of primary osteoporosis and other metabolic bone diseases. This study was designed to assess the effect of 17-β estradiol (E2) treatment and angiotensin converting enzyme inhibitor (ACEI), captopril, on osteoporosis induced by ovariectomy in rats and discussing the role of OPG/RANKL ratio in their action. Thirty two adult female rats were divided into four equal groups. Group I: control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Treatment of ORX mice with captopril significantly suppressed these changes of CAII, MMP-9 and OPG/RANKL. Similar results were reported by others that captopril increased the ratio of OPG/RANKL in bone [18] and serum [33] of OVX rats. Both MMP-9 and CAII, produced from osteoclasts, are enzymes to dissolve organic component and inorganic substance of bone, respectively [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Treatment of ORX mice with captopril significantly suppressed these changes of CAII, MMP-9 and OPG/RANKL. Similar results were reported by others that captopril increased the ratio of OPG/RANKL in bone [18] and serum [33] of OVX rats. Both MMP-9 and CAII, produced from osteoclasts, are enzymes to dissolve organic component and inorganic substance of bone, respectively [27].…”
Section: Discussionsupporting
confidence: 92%
“…Of noted, the recent studies demonstrated that captopril repaired cortical morphometric features [18] and improved cortical bone thickness [33] in OVX rats, while, the potential effect of captopril on cortical bone in ORX animals, such as the middle-shaft of tibia and femur, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased osteoprotegerin (OPG)/receptor activator of nuclear factor-kappa B ligand (RANKL) ratio was reported after ACEi in ovariectomized rats [27]. Anti-resorptive effects of ACEi through anti-osteoclastogenic activities reported in other [89] along with the increased OPG/RANKL ratio explains why use of ACEi would be associated with decreased bone loss, as observed in our study.…”
Section: Discussionsupporting
confidence: 75%
“…ACE inhibitors have been widely used in the treatment of hypertension and are the first drugs of interest to focus on the effects of RAAS inhibitors on bone metabolism. Numerous animal experiments 11,[13][14][15][16][17] and clinical studies 9,[18][19][20][21][22][23][24][25] have shown that ACE inhibitors reduce bone loss, improve BMD, increase bone biomechanical strength, reduce fracture risk, and accelerate fracture healing.…”
Section: Ace Inhibitorsmentioning
confidence: 99%